INTONASI PENGUCAPAN MADḤ AN-NABĪY PADA KITAB MAULID BARZANJI OLEH H. SUDIRMAN SEMMA' (SUATU ANALISIS FONEMIK) - Husaeri, Muhammad; Halim, Abdul (Al-Syamail: Jurnal Bahasa dan Sastra Arab, 2024)
The recitation of the Barzanji book is not a tradition that must be performed by Muslims, nor is it a ritual that must be observed every Prophet’s birthday. The purpose of reciting the Barzanji book is merely to derive wisdom and enhance the love of Muslims for their Prophet, making him a role model in their daily lives. The researcher was intrigued to explore the extent to which the tone or intonation of the Barzanji recitation, particularly in Madḥ An-Nabīy, affects its listeners. Thus, the researcher conducted a study entitled "Intonation of Madḥ An-Nabīy Recitation in the Maulid Barzanji Book by H. Sudirman Semma' (A Phonemic Analysis)." To collect information, this study employed a descriptive qualitative approach using phonemic analysis and interviews. The researcher applied an interactive data analysis model as described by Miles and Huberman. The theoretical framework used was the maqam theory popularized by Safiyuddin al-Urmawi. The findings of this study concluded that the use of maqam influences the understanding and experience of listeners. Maqam Bayātī conveys a soothing tone, Maqam Rāst presents a strong and majestic tone, while Maqam Sīkāh offers a soft and touching tone. The appropriate use of maqam in Barzanji recitation is crucial to effectively convey the meaning of Madḥ An-Nabīy, highlighting the need for education and training on maqam and text to achieve optimal results.